Paleogeographic reconstruction of the North China Craton in the supercontinent Nuna/Columbia: paleomagnetic and geological constraints - Wang, Chong (Curtin University, 2019)
The North China Craton has abundant Precambrian geological records, but its positions in the two supercontinents are still controversial. Detailed geochronological, geochemical, rock magnetic and paleomagnetic analyses have been carried out. The ~1.24–1.21 Ga magmatism in this craton indicates a LIP caused by a mantle plume. Comparable coeval paleopoles, APWPs and geological histories for the North China and proto-Australian cratons suggest their possible connection during ~1.78–1.32 Ga, but separation after that time.